2003
DOI: 10.1124/dmd.31.5.652
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Human UGT2B7 and 2B15 in Rofecoxib Metabolism

Abstract: ABSTRACT:O-Glucuronidation of 5-hydroxyrofecoxib is the major biotransformation pathway of rofecoxib in human, rat, and dog. The glucuronide conjugate is also involved in the reversible metabolism of rofecoxib in rat and human. Atypical bimodal phenomena were observed in their plasma concentration-time curves with a large variability among different human subjects. It is unclear which family members of human UDP-glucuronosyltransferases (UGT) are involved in the formation of the glucuronide. O-Glucuronidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Glucuronidation of BMS-204352 at the amide nitrogen represents a newly identified glucuronidation reaction by UGT2B7. UGT2B7 has been demonstrated to conjugate many drugs including morphine (Coffman et al, 1997), zidovudine (Barbier et al, 2000), epirubicin (Innocenti et al, 2001), estrogens and retinoic acid (Czernik et al, 2000), diclofenac (King et al, 2001), and rofecoxib (Zhang et al, 2003b). These reactions represent glucuronidations by UGT2B7 at nucleophilic functional groups of oxygen (carboxylic acid, phenol, and primary and secondary alcohols).…”
Section: Discussionmentioning
confidence: 99%
“…Glucuronidation of BMS-204352 at the amide nitrogen represents a newly identified glucuronidation reaction by UGT2B7. UGT2B7 has been demonstrated to conjugate many drugs including morphine (Coffman et al, 1997), zidovudine (Barbier et al, 2000), epirubicin (Innocenti et al, 2001), estrogens and retinoic acid (Czernik et al, 2000), diclofenac (King et al, 2001), and rofecoxib (Zhang et al, 2003b). These reactions represent glucuronidations by UGT2B7 at nucleophilic functional groups of oxygen (carboxylic acid, phenol, and primary and secondary alcohols).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have shown that the D85Y polymorphism affects oxazepam glucuronidation, it is not yet apparent whether other clinically important substrates of UGT2B15, such as E-4-hydroxytamoxifen (Nishiyama et al, 2002) and 5-hydroxyrofecoxib (Zhang et al, 2003) will be affected to a similar degree. Indeed, our previous work using recombinant D85 and Y85 variants indicates that the magnitude of the effect could be substrate dependent in that a greater than 10-fold difference between variants was observed for naringenin glucuronidation, compared with a 5-fold difference for oxazepam glucuronidation, whereas there was less than a 2-fold difference for dihydrotestosterone glucuronidation (Court et al, 2002).…”
Section: Ugt2b15 Pharmacogenetics 661mentioning
confidence: 99%
“…Pharmaceutical substrates of UGT2B15 that have been identified include oxazepam, E-4-hydroxytamoxifen, 5-hydroxyrofecoxib, eugenol, 8-hydroxyquinoline, phenolphthalein, 4Ј-hydroxyphenytoin, and nandrolone (Green et al, 1994;Court et al, 2002;Nishiyama et al, 2002;Kuuranne et al, 2003;Zhang et al, 2003). Oxazepam, a commonly used 1,4-benzodiazepine anxiolytic drug, is of considerable interest because it is cleared primarily by glucuronidation and has been used extensively as an in vivo probe of drug glucuronidation in people (Greenblatt et al, 1980(Greenblatt et al, , 1984Greenblatt, 1981;Sonne, 1993).…”
mentioning
confidence: 99%
“…According to the literature, the UGT 2B15 isoform could be investigated with bisphenol A (Hanioka et al, 2008), HMMA (Shoda et al, 2009) or 5-hydroxyrofecoxib (Zhang et al, 2003). The latter substrate was not assessed because of its light sensitivity.…”
Section: Selection Of Substratesmentioning
confidence: 99%